2011
DOI: 10.1111/j.1600-0854.2011.01163.x
|View full text |Cite
|
Sign up to set email alerts
|

SNARE Proteins Underpin Insulin‐Regulated GLUT4 Traffic

Abstract: Delivery of the glucose transporter type 4 (GLUT4) from an intracellular location to the cell surface in response to insulin represents a specialized form of membrane traffic, known to be impaired in the disease states of insulin resistance and type 2 diabetes. Like all membrane trafficking events, this translocation of GLUT4 requires members of the SNARE family of proteins. Here, we discuss two SNARE complexes that have been implicated in insulin-regulated GLUT4 traffic: one regulating the final delivery of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
1
43
0
1
Order By: Relevance
“…Sec1/Munc18 (SM) proteins are key regulators of membrane traffic exerting their effect through their cognate SNARE proteins, but their precise mode of action is not understood (3). The Munc18c SM protein binds to Sx4 and is required for insulin-regulated delivery of GLUT4 to the surface of fat and muscle cells (2). Intriguingly, Munc18c is phosphorylated in response to insulin, with Tyr521 being a direct target of the activated insulin receptor (4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sec1/Munc18 (SM) proteins are key regulators of membrane traffic exerting their effect through their cognate SNARE proteins, but their precise mode of action is not understood (3). The Munc18c SM protein binds to Sx4 and is required for insulin-regulated delivery of GLUT4 to the surface of fat and muscle cells (2). Intriguingly, Munc18c is phosphorylated in response to insulin, with Tyr521 being a direct target of the activated insulin receptor (4)(5)(6).…”
mentioning
confidence: 99%
“…Cell surface delivery of GLUT4 is mediated by a SNARE complex containing the plasma membrane-localized syntaxin4 (Sx4) and SNAP23 t-SNAREs and the VAMP2 v-SNARE (2). SNARE complex formation contributes to specificity of membrane traffic and also provides energy for bilayer fusion (3).…”
mentioning
confidence: 99%
“…The identification of v-SNARE proteins within purified GSVs [8] provided the first evidence that GLUT4 translocation requires SNARE proteins (reviewed in [9]). Subsequent studies have indicated the VAMP2 (vesicleassociated membrane protein 2) isoform as being the key v-SNARE in GSVs (reviewed in [9], but, for an alternative view, see [10]).…”
Section: Glut4 Trafficking Uses Snare Proteinsmentioning
confidence: 99%
“…Disrupting the function of these molecules (e.g. using antibody microinjection, transgenic knockout or siRNA approaches) supports a role for these proteins in the insulin-stimulated delivery of GLUT4 to the cell surface (see, for example, [9,[11][12][13]). Consistent with this, Sx4/SNAP23-containing liposomes could fuse with liposomes containing VAMP2, providing functional evidence that this SNARE combination is sufficient to drive membrane fusion in vitro [14].…”
mentioning
confidence: 98%
See 1 more Smart Citation